Optimizing the initial tacrolimus dosage in Chinese children with lung transplantation within normal hematocrit levels - Hu, Ke; He, Su-Mei; Zhang, Cun; Zhang, Yi-Jia; Gu, Qian; Shi, Hao-Zhe; Wang, Dong-Dong (Frontiers in Pediatrics, 2024)
Background: Initial tacrolimus dosage is undefined in Chinese pediatric lung transplant patients with normal hematocrit values. The purpose of this study is to optimize the initial dose of tacrolimus in Chinese children undergoing lung transplantation and presenting with normal hematocrit. Methods: The present study is based on a published population pharmacokinetic model of tacrolimus in lung transplant patients and uses Monte Carlo simulating to optimize the initial tacrolimus dosage in Chinese children with lung transplantation within normal hematocrit. Results: Within normal hematocrit, for children with lung transplantation who do not carry CYP3A5*1 and no coadministration with voriconazole, the dosages of tacrolimus, 0.02, 0.03 mg/kg/day splitted into two dosages are recommended for children whose weights are 10-32, 32-40 kg, respectively. For children with lung transplantation who carry CYP3A5*1 and no coadministration with voriconazole, the dosages of tacrolimus, 0.02, 0.03, 0.04 mg/kg/day splitted into two dosages are recommended for children whose weights are 10-15, 15-32, 32-40 kg, respectively. For children with lung transplantation who do not carry CYP3A5*1 and coadministration with voriconazole, the dosages of tacrolimus, 0.01, 0.02 mg/kg/day splitted into two dosages are recommended for children whose weights are 10-17, 17-40 kg, respectively. For children with lung transplantation who carry CYP3A5*1 and coadministration with voriconazole, the dosage of tacrolimus, 0.02 mg/kg/day splitted into two dosages are recommended for children whose weights are 10-40 kg, respectively. Conclusions: It is the first time to optimize the initial tacrolimus dosage in Chinese children with lung transplantation within normal hematocrit.